Pengaruh Penggunaan Mulsa Jerami Pada Sistem Tumpang Sari Tanaman Jagung Manis (Zea Mays saccharata Sturt) dan Kacang Kedelai (Glycine max (L) Merill) Terhadap Pertumbuhan dan Produksi - Tutik Nugrahini (Agrifarm : Jurnal Ilmu Pertanian, 2012)
Influence of Straw Mulch on intercropping system Crop Sweet Corn (Zea mays saccharata Sturt) and Soybean (Glycine max (L) Merrill) on Growth and Production. The aim of research to determine the effect of mulching straw on intercropped plants sweet corn (Zea mays saccharata Sturt.) And soybean (Glycine max (L) Merrill) on the growth and production. Research dilakanakan for 4 months starting from May to August of 2010, starting from land preparation to harvest. Location of research carried out in the village of Muara Bengkal ngayau East Kutai. This study was conducted using the Draft Plots Separated (RPT) with analysis of 2 x 5 and each -masing treatment was repeated 4 times. As the main plot (main plot) is a straw mulch consisting of two levels, namely: mo = without straw mulch, m1 = with straw mulch. Meanwhile, as the subplots (sub plot) is the use of intercropping systems (P) consists of 5 levels:: p1 = soybean monoculture, p2 = sweet corn monoculture, p3 = intercropping soybean + maize dibarisan middle, p4 = intercropping 3 lines corn among soybean, p5 = intercropping two rows of corn beside the left and right of the soybean crop. The results showed a significant effect of straw mulching treatment. Treatment cropping system significantly. Combination treatment with straw mulching intercropping system had no significant effect.